The impacts of seasonal variation and climate on food utilization in a population of critically endangered cotton‐top tamarins (Saguinus oedipus) in Colombia: A 22‐year longitudinal study. Issue 8 (20th July 2022) - Savage, A.; Snowdon, C. T.; Soto, L.; Castro, J.; Medina, F.; Emeris, G.; Garcia, L. C.; Guillen, R.
Abstract: To examine how precipitation patterns and climate change impact feeding choices made by a population of critically endangered cotton‐top tamarins ( Saguinus oedipus ), we examined 22 years of feeding data (1999–2020) from 21 groups collected at Parque Natural Regional Bosque Seco El Ceibal Mono Tití in Santa Catalina, Colombia. We describe the diet and examine the role of seasonal rainfall and annual variation in rainfall on diet. Rainfall is highly seasonal (mean annual rainfall 1562 mm [range 940–2680 mm]) with a dry, early rainy, and late rainy season in each year. Over 80 species of plants formed part of the fruit, nectar, and exudate components of the diet. Fruits, although available year‐round, were more commonly available and consumed during the late rainy seasons (August–November). Exudates were consumed more frequently in the dry season (December–March) and invertebrate consumption was stable across the year. Nectar feeding from a single species ( Combretum fruticosum ) peaked in November. Rainfall varied over the years, with 13 years exceeding the 99% confidence intervals for mean rainfall. Ten of these extreme years (both drought and extremely wet) occurred in the last 11 years. Fruit consumption did not vary between extreme and average years, but cotton‐top tamarins consumed more invertebrates and exudates in wet years. Presently, cotton‐top tamarins appear to be able to cope with these extreme variations in rainfall due to their highly varied diet. However, the forests that these primates depend upon for survival are threatened by human exploitation making it critically important to maintain a generalist feeding strategy for survival as many fruiting trees that compose a large proportion of the diet are removed. As conservation efforts continue, plant species consumed by cotton‐top tamarins provide useful data when selecting species for habitat restoration programs. Abstract : Cotton‐top tamarins consume a variety of foods with food groups ingested varying seasonally. Clockwise from upper left: Cotton‐top tamarin feeding on Allophylus racemosus, licking nectar of Combretum fruticosum, face covered in C. fruticosum pollen, cotton‐top tamarin feeding on a spider, and catching an insect. Copyright: used with permission of Suzy Estzerhas & Fundación Proyecto Tití. Highlights: Cotton‐top tamarins have a diverse diet consisting of fruits from trees, shrubs, and lianas as well as a variety of invertebrates, exudates, and nectar, feeding less frequently on flowers, meristems, fungi, cactus, and palms.